Optimal paraformaldehyde levels for disinfection of eggs used in vaccine production - Iasmin Papile dos Santos; Giancarlo Rieger; Rodrigo Garófallo Garcia; Jean Kaique Valentim; Fabiana Ribeiro Caldara; Ariane de Oliveira Troguilho; Sarah Sgavioli (Poultry Science)
The objective of this study was to evaluate the effects of paraformaldehyde levels on the disinfection of fertile eggs from breeders intended for vaccine production. A total of 4,368 fertile eggs were divided into seven treatment groups: nondisinfected eggs and eggs disinfected with 0, 2, 3, 4, 5, or 6 g/m³ of paraformaldehyde. Disinfection was carried out by fumigation, followed by incubation. On the 10th day of incubation, various parameters were measured, including egg mass loss, absolute and relative weights of the embryo and yolk sac, embryo length, embryonic mortality, and fertility. Bacterial counts were also assessed at three points: before disinfection, one hour after disinfection, and on the 10th day of incubation. Results showed that eggs disinfected with paraformaldehyde had significantly lower bacterial counts compared to nondisinfected eggs. One hour after disinfection, treatments without fumigation or those with fumigation without paraformaldehyde exhibited 100% of bacterial counts exceeding 300 CFU, while the treatment with 2 g/m³ of paraformaldehyde had 83.33% of bacterial counts exceeding 300 CFU. Higher paraformaldehyde levels significantly reduced bacterial counts, with the treatment of 3 g/m³ being the most effective, where only 8.33% of samples had bacterial counts exceeding 300 CFU. The optimal concentration for achieving the lowest bacterial counts was estimated to be 6.07 g/m³. In terms of egg mass, nondisinfected eggs experienced greater mass loss compared to fumigated eggs. Additionally, the best embryo length was observed at a concentration of 2.67 g/m³ of paraformaldehyde. Based on these findings, it is recommended to use 6.07 g/m³ of paraformaldehyde to effectively reduce bacterial contamination in fertile eggs used for vaccine production.